2022
DOI: 10.1159/000523961
|View full text |Cite
|
Sign up to set email alerts
|

Desidustat in Anemia due to Non-Dialysis-Dependent Chronic Kidney Disease: A Phase 3 Study (DREAM-ND)

Abstract: <b><i>Background:</i></b> Desidustat, an oral hypoxia-inducible factor prolyl hydroxylase inhibitor, is being developed to treat anemia in patients with chronic kidney disease (CKD) without dialysis dependency. <b><i>Methods:</i></b> In total, 588 patients with a clinical diagnosis of anemia due to CKD without dialysis need and with baseline hemoglobin of 7.0–10.0 g/dL (inclusive) were randomized in a 1:1 ratio to receive either desidustat 100 mg oral tablets thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…The remaining Phase 3 RCTs in ND-CKD population had an active treatment with ESA as the control arm. These studies testified the non-inferiority of roxadustat [37,38], molidustat [39,40], daprodustat [41], enarodustat [42], vadadustat [43,44] and desidustat [45] in comparison with darbepoetin alfa. Non-inferiority was confirmed independently from the parameter measured during the evaluation period as the primary endpoint (either change from baseline of Hb levels, the between-arm difference of mean Hb level or achieved mean Hb) (Table 1).…”
Section: Trials In Non-dialysis Ckdmentioning
confidence: 98%
See 4 more Smart Citations
“…The remaining Phase 3 RCTs in ND-CKD population had an active treatment with ESA as the control arm. These studies testified the non-inferiority of roxadustat [37,38], molidustat [39,40], daprodustat [41], enarodustat [42], vadadustat [43,44] and desidustat [45] in comparison with darbepoetin alfa. Non-inferiority was confirmed independently from the parameter measured during the evaluation period as the primary endpoint (either change from baseline of Hb levels, the between-arm difference of mean Hb level or achieved mean Hb) (Table 1).…”
Section: Trials In Non-dialysis Ckdmentioning
confidence: 98%
“…Only four studies (three with roxadustat and one with desidustat) reported data on HrQoL, by using the Short Form 36 (SF-36) vitality (VT) and physical functioning (PF) sub-scores. These studies disclosed no significant difference from placebo [34,35] nor from darbepoetin alfa [37,45]. However, only the study with desidustat reported an analysis of the increase of the quality-of-life score during treatment, showing similar improvement of SF-36 from baseline with desidustat and darbepoetin alfa [45].…”
Section: Quality Of Lifementioning
confidence: 99%
See 3 more Smart Citations